Antibiotic susceptibility patterns of pathogenic bacteria Iiolated from the surface of tables in local restaurants in Dhaka city - Islam, Tamanna; Toma, Tanjila (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2024.